HUMAN CAPITAL DEVELOPMENT AND EDUCATIONAL ADVANCEMENT IN NIGERIA: REALITIES AND WAY FORWARD. - OBIZUE, MIRIAN N.; ENOMAH , SYLVESTER (Int’l Journal of Education Research and Scientific Development, 2025)
Human capital development encompasses the enhancement of intellectual, physical, and emotional capacities within a population, fostering individual empowerment, national progress, and economic sustainability. It is a widely accepted notion in development economics that human capital, particularly when strengthened through quality education, serves as the foundation for sustainable economic growth, technological advancement, social stability, and poverty reduction. Education is the primary vehicle for this transformation, equipping individuals with the necessary skills, knowledge, and competencies to effectively engage in an increasingly complex and technologically driven global economy. In Nigeria, however, significant barriers continue to impede the realization of a robust human capital development framework. Despite various educational reforms and increased investments in the education sector, the country grapples with deep-seated challenges, including chronic underfunding, infrastructural decay, curriculum deficiencies, and stark socio-economic inequalities that hinder equal access to quality education. These structural deficiencies weaken Nigeria’s capacity to cultivate a competitive workforce and exacerbate long-term developmental setbacks such as high unemployment, low productivity, and economic stagnation. This paper critically examines the intricate relationship between human capital development and educational advancement in Nigeria the realities and way forward, providing an in-depth analysis of how investments in education, policy interventions, and systemic inefficiencies impact national productivity and economic growth. By drawing on theoretical perspectives, it argues that Nigeria’s current educational strategies fall short of fostering a globally competitive labour force. Furthermore, it explores the roles of key stakeholder including the government, private sector, and individuals in addressing the existing gaps and implementing strategic interventions for long-term educational and economic reform. Ultimately, this paper emphasizes the urgent need for a holistic approach to education reform, integrating policy consistency, infrastructural development, curriculum modernization, and equitable access to learning opportunities as a way forward.